Leveraging foundation and large language models in medical artificial intelligence - Io Nam Wong; Olivia Monteiro; Daniel T. Baptista-Hon; Kai Wang; Wenyang Lu; Zhuo Sun; Sheng Nie; Yun Yin; Jing Ni (Chinese Medical Journal)
Abstract. Recent advancements in the field of medical artificial intelligence (AI) have led to the widespread adoption of foundational and large language models. This review paper explores their applications within medical AI, introducing a novel classification framework that categorizes them as disease-specific, general-domain, and multi-modal models. The paper also addresses key challenges such as data acquisition and augmentation, including issues related to data volume, annotation, multi-modal fusion, and privacy concerns. Additionally, it discusses the evaluation, validation, limitations, and regulation of medical AI models, emphasizing their transformative potential in healthcare. The importance of continuous improvement, data security, standardized evaluations, and collaborative approaches is highlighted to ensure the responsible and effective integration of AI into clinical applications.